Urgensi Uzlah dalam Realita Kehidupan Modern Sebagai Benteng Keimanan bagi Peserta Didik - Eny Apri Winarni; Hajam Hajam; Mumun Munawaroh; Moh Ali (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The development of modern life, marked by rapid technological advances, cultural globalization, and the dominance of materialism and hedonism, has given rise to various spiritual and moral issues in human life. These conditions have implications for the weakening of faith orientation, moral degradation, and the rise of individualism and pragmatism. This article aims to analyze the urgency of the concept of uzlah in facing the realities of modern life and its relevance in the context of Islamic Religious Education. This research uses a qualitative approach with library research methods, through a literature review of classical Sufism books, scientific articles, and relevant previous research results. Data analysis techniques are carried out descriptively and analytically to explore the meaning, values, and implementation of uzlah contextually. The results of the study indicate that uzlah is not interpreted as total isolation from social life, but rather as an effort to control oneself, guard the heart, selectivity in social interactions, and strengthen spiritual awareness in the midst of modern life. In the context of Islamic Religious Education, uzlah has strategic implications as a foundation for spiritual development and strengthening the morals of students so that they are able to face the challenges of the times without losing their Islamic identity. Thus, uzlah remains relevant as a spiritual and educational approach to addressing the moral and spiritual crises of modern society.